Regional disparities and spatial convergence of multidimensional energy poverty in Indonesia - A'mal, Ikhlasul; Kartiasih, Fitri (Jurnal Ekonomi Indonesia, 2025)
Energy plays a fundamental role in driving global sustainability, encompassing social, economic, and environmental dimensions. The issue of access to adequate and affordable modern energy remains a crucial problem in various countries, including Indonesia. This condition reflects energy poverty, which has a widespread impact on all aspects of community life. This study investigates the convergence of energy poverty across provinces in Indonesia during the period 2016–2024, using balanced panel data covering 306 observations. This analysis utilizes 34 provinces to ensure data consistency throughout the research period, particularly for the development of the Multidimensional Energy Poverty Index (MEPI). Sigma convergence is assessed based on the evolution of cross-sectional variation in MEPI, while beta convergence is tested using spatial dynamic panel analysis. The research results indicate that energy poverty across provinces experienced both sigma and beta convergence. Per capita GRDP, urbanization rate, energy prices, higher education level, and regional spatial influence play an important role in accelerating the process of energy poverty convergence. Based on these findings, the government is expected to strengthen policies that support the expansion of access to modern energy, as well as encourage the role of socioeconomic factors to accelerate the process of energy equalization across regions.